Factors Affecting Inadequate Empirical Antimicrobial Therapy and the Clinical Course of Upper Urinary Tract Infections in Elderly Patients: A Multicenter Study - (:unkn) unknown (GALENOS YAYINCILIK, 2020)
Introduction: In this study, we aimed to determine the risk factors associated with inadequate empirical antibiotherapy (IEAT) and hospital-related mortality in elderly patients being treated for upper urinary tract infections (UTI). Materials and Methods: This study included individuals aged 65 years and over who were hospitalized after being diagnosed of community-acquired UTI or community-onset healthcare-associated UTI and followed-up in clinics and/or intensive care units (ICU) of 33 hospitals between March and September 2017. Results: A total of 525 patients (48% males; mean age: 76.46 +/- 7.93 years) were included in the study. Overall, 68.2% of the patients were hospitalized through the emergency department and 73.9% of patients were followed-up for pyelonephritis. Gram-negative, Gram-positive, and Gram-negative and positive mix growths were determined in 88%, 9.3%, and 2.7% of urine cultures, respectively. Fifty-six (10.7%) of the patients died. In multivariate analysis, the presence of chronic obstructive pulmonary disease [Odds ratio (OR): 2.278], age 85 years and over (OR: 2.816), admission to the ICU (OR: 14.831), and IEAT (OR: 2.364) were independent factors that significantly affected mortality. The presence of a urinary catheter, being followed-up in the ICU, benign prostate hypertrophy, use of antibiotics other than piperacillin-tazobactam and carbapenem were determined as independent factors that significantly affected IEAT (p<0.05). Conclusion: In our study, we found a direct correlation between IEAT and mortality. Therefore, knowing the most frequent microorganisms and antibiotic susceptibility profiles observed in the UTI of elderly patients may help to decrease the mortality and morbidity associated with these infections.
Keywords: Urinary tract infection; empirical; antibiotherapy; mortality; RISK-FACTORS; COMMUNITY; PREVALENCE; PROGNOSIS